2019
DOI: 10.22331/q-2019-09-09-185
|View full text |Cite
|
Sign up to set email alerts
|

Two-Qubit Pure Entanglement as Optimal Social Welfare Resource in Bayesian Game

Abstract: Entanglement is of paramount importance in quantum information theory. Its supremacy over classical correlations has been demonstrated in a numerous information theoretic protocols. Here we study possible adequacy of quantum entanglement in Bayesian game theory, particularly in social welfare solution (SWS), a strategy which the players follow to maximize sum of their payoffs. Given a multi-partite quantum state as an advice, players can come up with several correlated strategies by performing local measuremen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…While investigating generalized NS correlations, a number of games have been studied where supra-quantum NS correlations outperform optimal quantum winning strategies. [16,20,[45][46][47][48][49][50] There also exist games where quantum resources are as good as generalized NS correlations. [51][52][53] On the other hand, it has been shown that even a generalized probabilistic local model can outperform quantum theory by allowing stronger "time-like" correlation.…”
Section: On the Composite System ℂmentioning
confidence: 99%
“…While investigating generalized NS correlations, a number of games have been studied where supra-quantum NS correlations outperform optimal quantum winning strategies. [16,20,[45][46][47][48][49][50] There also exist games where quantum resources are as good as generalized NS correlations. [51][52][53] On the other hand, it has been shown that even a generalized probabilistic local model can outperform quantum theory by allowing stronger "time-like" correlation.…”
Section: On the Composite System ℂmentioning
confidence: 99%
“…Shared randomness (SR) is known to be an important resource in a number of applications, viz privacy amplification [22][23][24], simultaneous message passing [25], secret sharing and secret key generation protocol [26,27], classical simulation of quantum nonlocal statistics [28,30,51], Bayesian game theory [31][32][33][34], and communication complexity [35]. Among spatially separated parties, shared randomness can not be established free of cost.…”
Section: Introductionmentioning
confidence: 99%
“…In the late 90's quantum versions of it, that is, games in which players share quantum states and actions are translated into unitary operations, were first presented [5,6]. An active and diverse literature has then been established, connecting quantum correlations to various forms of games [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%